2016
DOI: 10.1051/e3sconf/20160704017
|View full text |Cite
|
Sign up to set email alerts
|

Long-term experiences with pluvial flood risk management

Abstract: Abstract. The awareness of pluvial (rain-related) flood risk has grown significantly in the past few years but pluvial flooding is not handled with the same intensity throughout Europe. A variety of methods and modelling technologies are used to assess pluvial flood hazard and risk and to develop suggestions for flood mitigation measures. A brief overview of current model approaches is followed by the description of a modelling methodology that has been developed throughout the last 15 years with the focus on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…In this study, overland flow is modelled using FloodAr-eaHPC, a raster-based 2D hydrodynamic model which uses a simplified hydraulic approach and a high-resolution DTM as input data. The model was developed by the Geographic Information System (GIS) consulting company geomer GmbH in Heidelberg to calculate inundation areas for the Rhine Atlas (ICPR, 2014) and has since been used in numerous studies for flood plain, dike breach, and pluvial flood modelling (Anders et al, 2016;Assmann et al, 2009Assmann et al, , 2013Fritsch et al, 2016;Kropáček et al, 2015). It is designed as an ArcGIS extension and makes use of some Spatial Analyst functions, although the main processing core works independently from ArcGIS (Geomer, 2013).…”
Section: Raster-based 2d Hydrodynamic Model Floodareamentioning
confidence: 99%
“…In this study, overland flow is modelled using FloodAr-eaHPC, a raster-based 2D hydrodynamic model which uses a simplified hydraulic approach and a high-resolution DTM as input data. The model was developed by the Geographic Information System (GIS) consulting company geomer GmbH in Heidelberg to calculate inundation areas for the Rhine Atlas (ICPR, 2014) and has since been used in numerous studies for flood plain, dike breach, and pluvial flood modelling (Anders et al, 2016;Assmann et al, 2009Assmann et al, , 2013Fritsch et al, 2016;Kropáček et al, 2015). It is designed as an ArcGIS extension and makes use of some Spatial Analyst functions, although the main processing core works independently from ArcGIS (Geomer, 2013).…”
Section: Raster-based 2d Hydrodynamic Model Floodareamentioning
confidence: 99%
“…There are relatively few studies on pluvial flood damage evaluation and loss modelling [21,22]. There is no common methodology of pluvial flood hazard and risk mapping [33]. Astrom et al [32] identified a knowledge gap in understanding future climate change scenarios and projections in decision making processes.…”
Section: Introductionmentioning
confidence: 99%
“…Due to an increased concentration of property, higher flood hazards lead to potentially higher rates of economic losses (Olsen et al 2015;Hattarai et al 2016). The planning of resilient cities needs to be based on the best available knowledge of flood hazards (Fritsch et al 2016), on probable economic impacts understood as the total cost of a disaster to the community and the environment (Carrera et al 2015), and on the risk to human lives and safety. The planning of resilient cities needs to be based on the best available knowledge of flood hazards (Fritsch et al 2016), on probable economic impacts understood as the total cost of a disaster to the community and the environment (Carrera et al 2015), and on the risk to human lives and safety.…”
Section: Introductionmentioning
confidence: 99%
“…If our cities are to be more resilient and better able to cope with the consequences of urban floods, they are expected to adopt sustainable strategies for adaption to new climatic and socioeconomic conditions (Serre et al 2010). Such an analytical and decision-making tool should include hazard assessment and risk mapping, and should help understand the impacts of floods on human lives, the infrastructure, the transport system, and the property damage (Fritsch et al 2016). Flood resilience management should ideally be supported by risk assessment tools that allow making decisions in conditions with a certain degree of uncertainty.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation